WOMEN ENTREPRENEURSHIP IN SMES: A CROSS-SECTIONAL STUDY ON FACTORS INFLUENCING THEIR SUCCESS IN THE MALDIVES - Zulham , Aishath Zidhuna; Hussain , Ibiwani Alisa; Singh , Jugindar Singh Kartar; Ahmad , Noraini; Chen , Lim Li (Electronic Journal of Business and Management, 2022)
Ekhane apnar deya paper-tir data extraction Copy-Paste Friendly format-e deya holo: Paper Number: 56 Title: WOMEN ENTREPRENEURSHIP IN SMES: A CROSS-SECTIONAL STUDY ON FACTORS INFLUENCING THEIR SUCCESS IN THE MALDIVES Abstract: This study aimed to investigate the influence of lack of access to finance, lack of access to networking, social expectation, and under-developed infrastructure on the success of women entrepreneurs amongst SMEs in the Maldives. The findings serve to explain the implications for women entrepreneurs, educate the business community, and improve policy-making. Primary data were gathered using an online survey questionnaire from 100 women entrepreneurs in the Maldives. Correlation analysis was conducted to test the relationship between predictors and success. Findings suggested that lack of access to finance, social expectation, and lack of networking were highly correlated with the success of these entrepreneurs. However, there was no evidence to support the impact of under-developed infrastructure on their success.